Rapid Releases and Testing Problems at the industry: A survey - Mascheroni, Maximiliano Agustín (2019)
Rapid releases and continuous software development are established practices in modern agile projects. The advantages of them are widely known across the software development community, but there are some studies which mention that there are still challenges to face. According to them, there are different open issues which are affecting the implementation of an adequate testing process. With the aim of validating if these problems are present in real projects, in this paper we present the results of a survey whose goal was to validate whether the industry is experiencing similar issues and their causes. The findings demonstrate that both the industry and academic side are aligned, and that there is still a need for processes and tools regarding the testing process in continuous development.